2006
DOI: 10.2138/am.2006.2215
|View full text |Cite
|
Sign up to set email alerts
|

Single-crystal elasticity of brucite, Mg(OH)2, to 15 GPa by Brillouin scattering

Abstract: The second-order elastic constants of brucite were determined by Brillouin scattering to 15 GPa in a diamond anvil cell. The experiments were carried out using a 4:1 methanol-ethanol mixture as pressure medium, and ruby as a pressure standard. Two planes, one perpendicular to the c axis (basal plane) and the other containing the c axis (meridian plane), were measured at room pressure and 10 elevated pressures. Individual elastic stiffnesses, aggregate moduli, and their pressure derivatives were obtained by fi … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 49 publications
(94 reference statements)
4
33
0
Order By: Relevance
“…Hill ) and shear (G P 3 Hill ) moduli for the trigonal phase, 46.7 and 36.4 GPa, respectively (36). The compressional (V P ) and shear (V S ) sound velocities for the tetragonal phase are also faster compared with the trigonal phase (Fig.…”
Section: Hillmentioning
confidence: 86%
See 1 more Smart Citation
“…Hill ) and shear (G P 3 Hill ) moduli for the trigonal phase, 46.7 and 36.4 GPa, respectively (36). The compressional (V P ) and shear (V S ) sound velocities for the tetragonal phase are also faster compared with the trigonal phase (Fig.…”
Section: Hillmentioning
confidence: 86%
“…(F) Calculated compressional/shear sound-wave velocities (circles/squares) for tetragonal Mg(OH) 2 (light-green symbol). Gray symbols refer to the experimentally determined sound velocity of brucite (36). Experimental data are given for the decomposition products periclase (MgO) (filled blue symbols) (63) and ice-VII (filled light-blue symbols: compression; white symbols: decompression) (50).…”
Section: Hillmentioning
confidence: 99%
“…Firstly, we indicate here that components of the elasticity tensor evaluated on the base of the relaxed P3m1 equilibrium geometry are well consistent with those predicted by experiment. [79][80][81] Secondly, one can see that elastic stability criteria of the trigonal system 82,83 certainly hold, i.e.…”
Section: B Stability Aspectsmentioning
confidence: 92%
“…Moreover, C 11 and C 13 at high pressures in Zha et al (1998) are much lower than our results. To independently determine all elastic constants of minerals in the orthorhombic system, previous studies have shown that measuring velocities using platelets close to basal planes, such as (100), (010), and (001), permits reliable derivations of all elastic constants (Jiang et al, 2006;Speziale et al, 2004;Wang et al, 2014), because some of the longitudinal and/or shear moduli in such planes are not covariance with other elastic constants and can be better constrained. Even so, it is still necessary to measure the velocity in two or three different crystal planes, because single-crystal elastic moduli of a given orthorhombic mineral may not be well constrained when lacking sufficient velocity measurements (Every, 1980;Fan et al, accepted).…”
Section: Single-crystal Elasticity Of Olivine At High P-tmentioning
confidence: 99%